Answer:
see explanation
Step-by-step explanation:
Given that the the difference of cubes is
a³ - b³ = (a - b)(a² + ab + b²)
Given
64
- 27 ← a difference of cubes
with a = 4x² and b = 3, thus
= (4x²)³ - 3³
= (4x² - 3)(16
+ 12x² + 9) ← in factored form
-22 is your answer because all you have to do is take 4 away from -18 and you get -22
Answer:
For f(x) = 2x + 3 and g(x) = -x 2 + 1, find the composite function defined by (f o g)(x)
(f o g)(x) = f(g(x))
= 2 (g(x)) + 3
= 2( -x 2 + 1 ) + 3
= - 2 x 2 + 5 Given f(2) = 3, g(3) = 2, f(3) = 4 and g(2) = 5, evaluate (f o g)(3)
Step-by-step explanation:
Answer:
e^2 -7 = x
Step-by-step explanation:
2=ln(x+7)
Raise each side to the base of e
e^2 = e^ln (x+7)
The e^ln cancel
e^2 = x+7
Subtract 7 from each side
e^2 -7 = x +7-7
e^2 -7 = x
Answer:
A. Area = 5/9 sq.meters
Step-by-step explanation:
Area = (lenght × widht)
![A=(\frac{5}{6} )(\frac{2}{3}) =\frac{(5)(2)}{(6)(3)} =\frac{10}{18}](https://tex.z-dn.net/?f=A%3D%28%5Cfrac%7B5%7D%7B6%7D%20%29%28%5Cfrac%7B2%7D%7B3%7D%29%20%3D%5Cfrac%7B%285%29%282%29%7D%7B%286%29%283%29%7D%20%3D%5Cfrac%7B10%7D%7B18%7D)
simplified
![A=\frac{5}{9}](https://tex.z-dn.net/?f=A%3D%5Cfrac%7B5%7D%7B9%7D)
Hope this helps